Effect of different sources of nitrogen on yield and yield attributes of transplanted rice under east and south coastal plains of Odisha - Pradhan, Abhijit; Behera, Biswajit; Chowdhury, Md Riton; Gulati, JML (ORYZA-An International Journal of Rice, 2020)
Integrated nutrient management (INM) plays an important role to maintain the soil health and improve crop productivity. A field experiment was conducted to study the effect of integrated nitrogen application on transplanted rice. The present investigation was laid out in randomised block design with 10 treatments. Growth parameters like plant height, dry matter accumulation varied significantly among different treatments and the highest value was recorded under the treatment T6 (75% N through fertilizer + 25% N throughvermicompost with full dose of P and K). All the yield attributing characters like panicles m-2, grains panicle-1 significantly varied under different treatments. Significantly, higher tiller m-2, grain panicle-1 and panicle length were recorded under T6. Similarly, significantly highest grain yield (4.93 t ha-1) and straw yield (6.01 t ha-1) were observed under T6. Thus, substituting a part of nitrogen fertilizer with organic manure improves soil quality and sustains the crop productivity.